Pernikahan dan Kehamilan di Luar Nikah Dalam Perspektif Hukum dan Fiqih - Burhanuddin; Hermawati (TAFAQQUH, 2023)
This research aims to examine and analyze extramarital relationships and pregnancies from two main perspectives: law and fiqh (Islamic law). The phenomena of extramarital relationships and pregnancies have become complex and controversial issues in modern society. This study will elucidate the legal and fiqh viewpoints on these issues and identify their similarities, differences, and implications within the contexts of law and religion. The research is based on a literature review methodology, involving an analysis of various literary sources such as books, articles, fatwas, and relevant legal documents. This analysis encompasses an understanding of the perspectives of positive law and Islamic law regarding extramarital relationships and pregnancies, as well as the potential legal and religious consequences that may arise from them. Additionally, this research will evaluate societal views on extramarital relationships and pregnancies and how these perspectives influence social actions and policies. The results of this research are expected to provide a deeper understanding of extramarital relationships and pregnancies from the perspectives of law and fiqh, offering valuable insights into addressing conflicts that may arise between positive law and religious values. This research may also contribute to the development of more inclusive and sustainable social policies related to these issues, taking into consideration relevant legal and religious aspects.